Two new species of Botryosphaeriaceae (Botryosphaeriales) and new host/geographical records - Rathnayaka, Achala R.; Thilini Chethana, K.w.; Phillips, Alan J.l.; Jones, E.b. Gareth (Phytotaxa, 2022)
Botryosphaeriaceae is the largest family in Botryosphaeriales, consisting of 22 genera. The family is worldwide in distribution and occurs on a wide variety of plant hosts. Botryosphaeriaceae includes endophytic, saprobic, and plant pathogenic species associated with canker and die-back diseases, most common on woody plants. The present study establishes two novel species of Dothiorella and new host and geographical records for species of Botryosphaeria, Dothiorella, Neodeightonia, and Sphaeropsis. Taxa were identified based on morphology coupled with phylogenetic analyses based on maximum likelihood and Bayesian analyses of SSU, LSU, ITS, tef1-α and β-tub sequences. The taxa are described and illustrated.